2016
DOI: 10.3928/1081597x-20161019-02
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Severe Interface Inflammation After Uneventful Small Incision Lenticule Extraction (SMILE)

Abstract: Stromal herpetic keratitis could be considered a potential differential diagnosis to this atypical lamellar keratitis after a SMILE procedure. [J Refract Surg. 2016;32(12):855-857.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…49 SMILE was first performed and pioneered by Sekundo et al There has only been one reported case of possible HSK post-SMILE. 50,51 The patient presented three days after undergoing SMILE with decreased vision, pain, and decreased corneal sensitivity. Notably, she had no signs of ulceration or discharge; fungal and bacterial cultures were negative.…”
Section: Post-smile Herpetic Ocular Diseasementioning
confidence: 99%
“…49 SMILE was first performed and pioneered by Sekundo et al There has only been one reported case of possible HSK post-SMILE. 50,51 The patient presented three days after undergoing SMILE with decreased vision, pain, and decreased corneal sensitivity. Notably, she had no signs of ulceration or discharge; fungal and bacterial cultures were negative.…”
Section: Post-smile Herpetic Ocular Diseasementioning
confidence: 99%